Two cases of congenital dysfibrinogenemia associated with thrombosis – Fibrinogen Praha III and Fibrinogen Plzeň - Kotlín, Roman; Reicheltová, Zuzana; Malý, Martin; Suttnar, Jiří; Sobotková, Alžbòta; Salaj, Peter; Hirmerová, Jana; Riedel, Tomáš; Dyr, Jan E. (Thrombosis and Haemostasis, 2009)
Congenital dysfibrinogenemia is a rare disease characterised by inherited abnormality in the fibrinogen molecule, resulting in functional defects. Two patients, a 26-year-old woman and a 61-year-old man, both with history of thrombotic events, had abnormal coagulation test results. DNA sequencing showed the heterozygous γY363N mutation (Fibrinogen Praha III) and the heterozygous Aα N106D mutation (Fibrinogen Plzeň), respectively. Fibrin polymerisation, after addition of either thrombin or reptilase, showed remarkably delayed polymerisation in both cases. Fibrinolysis experiments showed slower tPA initiated lysis of clots. SDS-PAGE did not show any difference between normal and Praha III and Plzeň fibrinogens. Both mutations had a significant effect on platelet aggregation. In the presence of either ADP or TRAP, both mutations caused the decrease of platelet aggregation. SEM revealed abnormal clot morphology, with a large number of free ends and narrower fibres of both fibrin Praha III and Plzeň. Praha III mutation was situated in the polymerisation pocket “a”. The replacement of the bulky aromatic side chain of tyrosine by the polar uncharged small side chain of asparagine may lead to a conformational change, possibly altering the conformation of the polymerisation pocket. The Plzeň mutation is situated in the coiled-coil connector and this replacement of polar uncharged asparagine residue by polar acidic aspartate changes the alpha-helical conformation of the coiled-coil connector;and may destabilise hydrogen bonds in its neighborhood. Although both mutations are situated in different regions of the molecule, both mutations have a very similar effect on fibrinogen functions and both are connected with thromboses.
Keywords: Dysfibrinogenemia; fibrinogen; missense mutation; pulmonary embolism; thrombosis